2008
DOI: 10.2967/jnumed.107.045138
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Imaging of bcl-2 Expression in Small Lymphocytic Lymphoma Using 111In-Labeled PNA–Peptide Conjugates

Abstract: The bcl-2 gene is overexpressed in non-Hodgkin's lymphoma (NHL), such as small lymphocytic lymphoma (SLL), and many other cancers. Noninvasive imaging of bcl-2 expression has the potential to identify patients at risk for relapse or treatment failure. The purpose of this study was to synthesize and evaluate radiolabeled peptide nucleic acid (PNA)-peptide conjugates targeting bcl-2 gene expression. An 111 In-labeled PNA complementary to the translational start site of bcl-2 messenger RNA was attached to Tyr 3 -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 35 publications
3
43
2
Order By: Relevance
“…This behavior is comparable to plain radiolabeled PNAs [23,24]. Conjugation of targeting peptide moieties to PNA significantly increases the kidney accumulation of PNA constructs [14,[17][18][19]29,30,44,87,88]. A preliminary SPECT study in a NMRI, nu/nu mouse was also performed with [ 99m Tc(CO) 3 (Dpa-PNA)].…”
Section: Biodistribution Studies Of [ 99m Tc(co) 3 (Dpa-pna)]mentioning
confidence: 92%
See 1 more Smart Citation
“…This behavior is comparable to plain radiolabeled PNAs [23,24]. Conjugation of targeting peptide moieties to PNA significantly increases the kidney accumulation of PNA constructs [14,[17][18][19]29,30,44,87,88]. A preliminary SPECT study in a NMRI, nu/nu mouse was also performed with [ 99m Tc(CO) 3 (Dpa-PNA)].…”
Section: Biodistribution Studies Of [ 99m Tc(co) 3 (Dpa-pna)]mentioning
confidence: 92%
“…In such constructs, the role of the PNA is to direct the bioconjugate to a specific mRNA -a unique or a uniquely over-expressed mRNA in a diseased cell -while the function of the radioactive probe is to allow imaging to possibly provide information on cellular gene expression pattern and detect molecular changes at relatively early stages [13,42]. Hence, a number of in vivo biodistribution/hybridization studies of radiolabeled PNAs were undertaken [14,[17][18][19][20]22,[24][25][26][27][28][29][30][31][32][33]36,39,41,[43][44][45][46]. The majority of these reports involved the use of 99m Tc, probably due its ideal nuclear properties and the convenient availability from a commercial generator [47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…In vivo imaging by microSPECT/ CT was also investigated and showed that the tumours could be imaged, and that imaging agreed with the biodistribution data. [99] Nanostructures using chemically modified oligonucleotide have been explored for use, for example, in nanotubes, arrays and machinery. Chaput et al demonstrated the use of glycol nucleic acids in the formation of two mirror image 4-helix junctions.…”
Section: Bioanalytical and Diagnostic Applicationsmentioning
confidence: 99%
“…Bcl-2 has been described as an oncogene whose overexpression results in tumorigenesis, suppression of apo-ptosis [16,17,18], and resistance to a number of cytotoxic drugs [19]. Downregulation of Bcl-2 mRNA in leukemic patients using antisense technology resulted in increased apoptosis and potentiation of the effect of antineoplastic drugs in these patients [20].…”
Section: Introductionmentioning
confidence: 99%